- #1

Oddbio

Gold Member

- 46

- 0

## Main Question or Discussion Point

I am trying to show that the laplacian:

[tex]L = -\frac{1}{4}F_{\mu\nu}F^{\mu\nu}[/tex]

can also be represented as:

[tex]L = \frac{1}{2}(\vec{E}^{2}-\vec{B}^{2})[/tex]

where [tex]F^{\mu\nu} = \partial{}^{\mu}A^{\nu} - \partial{}^{\nu}A^{\mu}[/tex]

and

[tex]F_{\mu\nu} = g_{\mu\alpha}F^{\alpha\beta}g_{\beta\nu}[/tex]

A is the scalar potential.

[itex]F^{\mu\nu}[/itex] is the antisymmetric field strength tensor.

But I cannot see how they are able to represent the first equation as the second equation.

Any advice would really help me a lot.

[tex]L = -\frac{1}{4}F_{\mu\nu}F^{\mu\nu}[/tex]

can also be represented as:

[tex]L = \frac{1}{2}(\vec{E}^{2}-\vec{B}^{2})[/tex]

where [tex]F^{\mu\nu} = \partial{}^{\mu}A^{\nu} - \partial{}^{\nu}A^{\mu}[/tex]

and

[tex]F_{\mu\nu} = g_{\mu\alpha}F^{\alpha\beta}g_{\beta\nu}[/tex]

A is the scalar potential.

[itex]F^{\mu\nu}[/itex] is the antisymmetric field strength tensor.

But I cannot see how they are able to represent the first equation as the second equation.

Any advice would really help me a lot.